INNOVATION - A STRATEGIC RESOURCE FOR THE DEVELOPMENT OF BUSINESS ORGANIZATIONS - V. L. Polyakov (Модернизация, инновация, развитие, 2016)
This paper discusses issues arising from the need to translate the Russian economy to innovative development. Essence and meaning of concepts such as innovation, innovation process, innovation management solution, the investment in relation to business organizations.